Assessing sleep quality in elite and junior cyclists - Javaloyes, Alejandro; Mateo-March, Manuel; Peña-González, Iván; Moya-Ramón, Manuel (Frontiers in Sports and Active Living, 2024)
In the pursuit of optimal recovery, the significance of sleep cannot be overstated for elite cyclists, including high-level cyclists within the junior category. This study aims to assess the sleep quality of elite athletes of different categories and disciplines, including junior. The sleep quality of 112 high-level cyclists (males n = 80; females n = 32) participating in endurance and sprint disciplines was evaluated using the Pittsburgh Sleep Quality Index (PSQI). A noteworthy 41% of both elite and junior cyclists displayed poor sleep quality. No significant differences were observed between elite and junior cyclists in terms of sleep quality, but there was a medium effect size, indicating greater sleep efficiency in junior cyclists (0.36 [0.16, 0.53]). Gender differences were found, with females exhibiting worse PSQI scores (males = 4.00 [2.25]; females 5.00 [3.00]; p = 0.035). Endurance cyclists spent more time in bed compared to cyclists from sprinting disciplines (8:30 [1.00] and 8:00 [1:03], respectively; p = 0.019). These findings reveal poor sleep habits, even among individuals classified as good sleepers by the PSQI, emphasizing the importance of preventing sleep disorders in cyclists. This study provides valuable insights into athlete sleep quality, encompassing various categories, genders, and cycling disciplines. In conclusion, elite cyclists demonstrate suboptimal sleep quality, suggesting the potential for interventions utilizing the PSQI. These findings advocate for the incorporation of sleep quality assessments into routine evaluations for athletes.